Análise de impactos de sistemas fotovoltaicos em redes de distribuição em condições de regime permanente - Dal Molin, Gustavo Dagios (2019)
An increase in the share of electric energy in the world has been gaining importance and presenting alternatives to meet the increase in energy demand. Within the various options, wind energy and solar energy are the most outstanding, encouraged by the advancement of technologies, concern for sustainability and increasingly competitive costs. Brazil follows, in general, these same international trends in relation to energy development. Through fiscal, economic and public policies that stimulate the growth of renewable sources, distributed solar photovoltaic generation has been highlighted, with a significant increase of its participation in the Brazilian electric energy generation. However, this increase requires studies that analyze the possible impacts that this may have on existing electricity distribution systems, for final consumers and distributors. Therefore, this study aims to analyze the main impacts in steady-state in a Brazilian real feeder considering probabilistic analyzes.For this, a literature review of these impacts was carried out. Then, OpenDSS® power flow analysis software was chosen, which at certain times was controlled via Matlab®. With this, a hypothetical grid and an real Brazilian feeder were characterized and modeled. Scenarios were elaborated, which led to the hypothetical grid to the deterministic analyzes. In the scenarios elaborated for the real feeder, probabilistic analyzes were performed based on Monte Carlo, in which random variables were used. Thus, the behavior of the average of the violations of the limits of the impacts with the growth of the penetration factor and allocation factor were presented. It was observed that when more random variables were considered, the violations occurred for lower penetration and allocation factors. The analyzed impacts were on voltage, current, losses, power factor and voltage unbalance.